Spatial variation in microbial communities associated with sea-ice algae in Commonwealth Bay, East Antarctica - Vadillo Gonzalez, Sebastian; Clark, Graeme F.; Johnston, Emma L.; Turney, Chris S. M.; Fogwill, Christopher J.; Steinberg, Peter D.; Marzinelli, Ezequiel M. (Microbiology Society, 2022)
Antarctic sea-ice forms a complex and dynamic system that drives many ecological processes in the Southern Ocean. Sea-ice microalgae and their associated microbial communities are understood to influence nutrient flow and allocation in marine polar environments. Sea-ice microalgae and their microbiota can have high seasonal and regional (>1000 km2) compositional and abundance variation, driven by factors modulating their growth, symbiotic interactions and function. In contrast, our knowledge of small-scale variation in these communities is limited. Understanding variation across multiple scales and its potential drivers is critical for informing on how multiple stressors impact sea-ice communities and the functions they provide. Here, we characterized bacterial communities associated with sea-ice microalgae and the potential drivers that influence their variation across a range of spatial scales (metres to >10 kms) in a previously understudied area in Commonwealth Bay, East Antarctica where anomalous events have substantially and rapidly expanded local sea-ice coverage. We found a higher abundance and different composition of bacterial communities living in sea-ice microalgae closer to the shore compared to those further from the coast. Variation in community structure increased linearly with distance between samples. Ice thickness and depth to the seabed were found to be poor predictors of these communities. Further research on the small-scale environmental drivers influencing these communities is needed to fully understand how large-scale regional events can affect local function and ecosystem processes.
Keywords: algae; Antarctic sea-ice; B09B iceberg; carbon cycle; Mertz Glacier; microbiome; nitrogen cycle and variability